These bones shall rise again : selected writings on early China - Keightley, David N.; Rosemont, Henry (Albany, New York : SUNY Press, 2014)
This book brings together in one volume many of teh author's seminal essays on the origins of early Chinese civilization. Written over a period of three decades and accessible to the non-specialist, these essays provide a wealth of information and insights on the Shang dynasty, traditionally dated 1766-1122 or 1056 BCE. Of all the eras of Chinese history, the Shang has been a particularly elusive one, long considered more myth than reality. A historian with a keen appreciation for anthropology and archaeology, the author has given us many descriptions of Shang life. Best known for his analysis of oracle bones, he has looked beyond the bones themselves and expanded his historical vision to ponder the lives of those who used them. What did the Shang diviner think he was doing? The temerity to ask such questions and the insights they have provided have been provocative and, at times, controversial. Equally intriguing have been the author's assertions that many of the distinctive features of Chinese civilization were already in evidence during the Shang, 3000 years ago. -- From publisher's website.
""S """"T ""; ""U ""; ""V ""; ""W ""; ""X ""; ""Y ""; ""Z ""
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: China -- History -- Han dynasty, 202 B.C.-220 A.D.; China -- History -- Qin dynasty, 221-207 B.C.; China -- History -- Shang dynasty, 1766-1122 B.C.; China -- History -- To 221 B.C.; China -- History -- Zhou dynasty, 1122-221 B.C.; Chine -- Histoire -- 202 av. J.-C.-220 (Dynastie des Han); Chine -- Histoire -- 221-207 av. J.-C. (Dynastie des Qin); Chine -- Histoire -- 1766-1122 av. J.-C. (Dynastie des Shang); Chine -- Histoire -- Jusqu'à 221 av. J.-C.; Chine -- Histoire -- 1122-221 av. J.-C. (Dynastie des Zhou); HISTORY / Asia / China; Han Dynasty (China); Qin Dynasty (China); Shang Dynasty (China); Zhou Dynasty (China); China; To 220; History